Ensuring Children’s Rights after Divorce in Indonesia: Religious Court Decisions on Nafkah Madiyah - Nasution, Hotnidah; Triana, Windy; Muchtar, Ahmad Rifqi (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Studies in various Muslim countries show that the fulfillment of child maintenance after divorce by fathers remains an issue. This paper examines the fulfillment of nafkah madiyah, or arrear maintenance for children, by the Religious Courts in Indonesia, especially after the issuance of Supreme Court Circular No. 2 of 2019. Relying on the analysis of ten Religious Court Decisions, this study finds that there have been inconsistencies in the Court Decisions in fulfilling the demand for nafkah madiyah submitted by mothers. The differences in the outcomes are caused by the different legal bases used by the judges and their consideration of men’s ability to fulfill the demands. The main reason for nafkah madiyah rejection is the judges’ arguments that maintenance costs are for children to take benefits from them (li al intifa’) and not for possession (li al tamlik). This means that if a father did not provide for his children in the past, his negligence does not become a debt to be paid in the future. Meanwhile, judges grant the request of nafkah madiyah because child maintenance is the father’s obligation. As in many cases, women are the primary carers of children after a divorce; ultimately, fulfilling nafkah madiyah is to protect not only children’s rights but also women’s rights. [Kajian terdahulu di beberapa negara Muslim menunjukkan bahwa pemenuhan nafkah anak oleh ayah masih menjadi masalah. Penelitian ini mengkaji pemenuhan nafkah terhutang (madiyah) untuk anak, oleh Pengadilan Agama di Indonesia, khususnya setelah lahirnya Surat Edaran Mahkamah Agung No. 2 Tahun 2019. Dengan analisis terhadap sepuluh Putusan Pengadilan Agama, studi ini menemukan bahwa terdapat inkonsistensi Putusan Pengadilan dalam memenuhi tuntutan nafkah madiyah yang dituntut oleh ibu. Perbedaan putusan tersebut disebabkan oleh perbedaan dasar hukum yang digunakan oleh para hakim dan pertimbangan mereka terhadap kemampuan laki-laki untuk memenuhi tuntutan tersebut. Alasan utama penolakan nafkah madiyah adalah argumen hakim bahwa biaya nafkah adalah untuk diambil manfaatnya oleh anak (li al intifa') dan bukan untuk dimiliki (li al tamlik). Artinya, jika seorang ayah tidak menafkahi anaknya di masa lalu, kelalaiannya itu tidak menjadi utang yang harus dibayar di masa depan. Sementara itu, hakim mengabulkan permohonan nafkah madiyah karena menganggap nafkah anak adalah kewajiban ayah. Sebagaimana dalam banyak kasus, perempuan adalah pengasuh utama anak setelah perceraian, pada akhirnya, pemenuhan nafkah madiyah adalah untuk melindungi tidak hanya hak anak tetapi juga hak-hak perempuan.]